Optical Wireless Communication: An Alternative Network Access Emerging Technology - Prof. Dr. Mohammad Faiz Liew Abdullah (2020)
There is an emerging technology with huge potential for the provision of pervasive and reliable next-generation communications networks known as optical wireless communications (OWC). An efficient wireless technologies can contribute to a range of transmission links essential for the heterogeneous networks of the future to support various communications services for indoor and outdoor with ever-increasing demands for higher data-transfer rates.